ANALISIS DATA PARAMETER HUJAN MENGUNAKAN FITUR GUIDE PADA MATLAB BERDASARKAN HASIL PENGUKURAN INSTRUMEN OPTICAL RAIN GAUGE DI LOKA PENGAMATAN ATMOSFER KOTOTABANG LAPAN - Soni Darma Laserio (PILLAR OF PHYSICS, 2014)
Optical Rain Gauge (ORG) is an instrument rainfall monitoring. Rainfall data analysis from ORG is use to determine the type of Oldeman climate classification. Rainfall data conditioning uses matlab then comparing the type and sub type climate of Oldeman. ORG has been installed in Kototabang (0.20S; 100.320 E). The research have three Resuls. First,ORG Receiver box measure rainfall by detecting osillation of light when the IRED output blocked by water droplets. Secondly, the user interface of rainfall data conditioning were made by Matlab GUIDE the features of Matlab. Third, the results of rainfall data analysis from 2010 and 2011 ORG-815 output data is the Oldeman climate types for Kototabang area. Oldeman climate type for 2010 data is  D1 type and the year 2011 is C2 type. Keywords: Rain, Parameter, Guide Fitur, Instrument, ORG